Theoretical Analysis of Improving Critical Thinking Skills of Students at Secondary Schools (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the theoretical foundations and strategies for enhancing critical thinking skills among secondary school students. It examines various cognitive theories and educational models that support the development of analytical reasoning, problem-solving, and decision-making abilities. By investigating existing literature, the paper identifies key teaching methods, curriculum design principles, and classroom practices that can foster critical thinking. Theoretical frameworks such as constructivism, metacognition, and active learning are discussed to highlight their roles in shaping students' intellectual independence.